2010
DOI: 10.1016/j.expneurol.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Transient elevation of adult hippocampal neurogenesis after dopamine depletion

Abstract: Degeneration of the midbrain dopaminergic neurons during Parkinson's disease (PD) may affect remote regions of the brain that are innervated by the projections of these neurons. The dentate gyrus (DG), a site of continuous production of new neurons in the adult hippocampus, receives dopaminergic inputs from the neurons of the substantia nigra (SN). Thus, depletion of the SN neurons during disease or in experimental settings may directly affect adult hippocampal neurogenesis. We show that experimental ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
(73 reference statements)
5
57
0
Order By: Relevance
“…TH activity is progressively decreased following the loss of dopamine neurons in the striatum as well as in the SN in the hypoxicischemia rodent model (Jakowec et al 2004). Brain damage decreases TH expression in the SN and striatum (Park and Enikolopov 2010). In this study, significantly decreased TH expression in the striatum and SN was observed in the rats of the hypoxic-ischemia group compared with those in the sham-operation group.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…TH activity is progressively decreased following the loss of dopamine neurons in the striatum as well as in the SN in the hypoxicischemia rodent model (Jakowec et al 2004). Brain damage decreases TH expression in the SN and striatum (Park and Enikolopov 2010). In this study, significantly decreased TH expression in the striatum and SN was observed in the rats of the hypoxic-ischemia group compared with those in the sham-operation group.…”
Section: Discussionsupporting
confidence: 51%
“…A previous study suggested that impairment of performance in hypoxic ischemia rats was due to learning and memory deficits (Anderson and Arciniegas 2010). Deficits in learning and memory following hypoxic ischemia are closely correlated with dopamine dysfunction in the nigrostriatal pathway and excessive cell proliferation in the hippocampus (Fan et al 2006;Park and Enikolopov 2010). Dopamine availability in both striatal and extrastriatal brain regions is known to be implicated in cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies support a role of the cholinergic system in the regulation of newborn neuron maturation and survival (Kaneko et al, 2006;Campbell et al, 2010) and modulation of their excitability that may facilitate information output to the CA3 (Vogt and Regehr, 2001). Likewise studies over the last decade suggest that dopamine contributes to proliferation of neural precursor cells in the subgranular zone (Höglinger et al, 2004;DomĂ­nguez-EscribĂ  et al, 2006;Park and Enikolopov, 2010), and modulates synaptic transmission and plasticity of GCs (Mu et al, 2011). Further investigation is necessary to understand the role of cholinergic and dopaminergic inputs during GC maturation.…”
Section: Discussionmentioning
confidence: 98%
“…Dopaminergic neurites contact progenitor cells in the subgranular zone (SGZ) (Höglinger et al, 2004) and form symmetric synapses with dendrites and perikarya of GCs (Milner and Bacon, 1989). It has been proposed that release of dopamine (DA) and the expression of DA receptors on neural precursor cells in SGZ could control aspects of neurogenesis (Diaz et al, 1997;Höglinger et al, 2004;Berg et al, 2013), although conflicting results have been reported (DomĂ­nguez-EscribĂ  et al, 2006;Park and Enikolopov, 2010). Furthermore, DA differentionally modulates excitatory synaptic transmission from the perforant path to GCs depending on developmental stage.…”
Section: Circuitry Of the Adult Dentate Gyrusmentioning
confidence: 99%
“…It will therefore be worthwhile to further assess whether the present results are associated with the enhanced or attenuated neurogenesis in the SN. Since MPTP can induce a transient increase in cell division in the SGZ of the DG (Park and Enikolopov, 2010), whether cells in the hippocampal DG are involved in the neurogenesis observed in the MPTP mouse model of PD should also be investigated.…”
Section: Discussionmentioning
confidence: 99%